An analysis of alternative soil, nutrient, and water management strategies. - Smith, Craig Matthew (Kansas State University, 2011)
The two topics addressed in this dissertation are both related to surface water quality. Reservoir sedimentation and water quality trading are examined from economic and environmental perspectives. Each topic and the resulting policy implications are relevant to stakeholders at the local, state, and federal levels. Reservoir sedimentation has been recognized as a major environmental, social, and economic issue in much of the Midwestern US. There is an effort to focus public and private funds to achieve the greatest return on the investment from soil erosion and sediment reduction strategies. How can physiographical and economic relationships within the watershed be quantified in such a way to provide insights into the selection of alternative management strategies? This study focuses on answering that question by integrating a physically-based watershed model with an economic analysis of alternative sedimentation reduction strategies for the case of Tuttle Creek Lake located in northeastern Kansas. Several key finding of this study are that both physiographical and economic factors must be considered for cost-effective conservation to occur. Considering these factors and targeting BMP implementation from 8 to 23 times more cost-effective than random implementation. If targeting cannot be done effectively or if “intangible” costs of BMP implementation are too large, dredging is likely to be more cost-effective. While this research compares the cost-effectiveness of various BMP implementation approaches in Kansas with dredging, the benefits associated with each of these strategies is not addressed. While there is substantial evidence that nonpoint sources have lower nutrient reduction costs than point sources, experience with water quality trading (WQT) reveals a common theme: little or no trading activity. These outcomes suggest the presence of obstacles to trading that were not recognized in the design of existing programs. To examine the ways that various market imperfections may impact the performance of a WQT market, an agent-based model is constructed, which simulates a hypothetical point-nonpoint market. This study first presents an overview of the concepts and simulation modeling technique used and then analyzes the effects of two prominent market impediments identified in the WQT literature: information levels and trading ratios. The results imply that if market designers feel that only a limited number of trades will be consummated, creating an institution that provides accessible information about buyers’ prices is preferred to providing information about sellers’ prices. Overall, more information is always better, but it becomes less important with higher trading ratios.
Keywords: Water; Soil; Market based; Conservation; Policy; Best management practice; Economics, Agricultural (0503); Environmental economics (0438); Natural Resource Management (0528)